Study on the economic viability of a photovoltaic plant in a higher education institution in the semi-arid region of Paraíba (Research, Society and Development, 2020)
This study aimed at analyzing the feasibility of the implantation of solar panels as a successful experience in the socio-environmental and economic area. A documentary and bibliographical survey was carried out for the theoretical basis of this final paper, as well as data collection at UFCG regarding the solar panels and information about the contract signed for the implementation of the photovoltaic system, as well as at the energy concessionaire, Energisa, to obtain the figures related to the campus's monthly electricity consumption. After this stage, an analysis was carried out between May and October of 2018, aiming at comparing the figures on energy consumption, with a view to verifying the economy and other benefits brought by the implementation of the 114 photovoltaic plates installed. Initially, it was estimated an annual savings of R$ 18,000.00 (eighteen thousand reais), but the figures found in the study have shown that consumption does not reach the value established in the contract (500 KW). The measures found in the analyzed period do not reach the contractual measure signed. The average of the results for the 06 months is 265.44 KW, which is much lower than the agreement signed between the institution and the energy company. In this way, it can be seen that the PV Plant of UFCG Pombal still does not present satisfactory results regarding the economic aspect, considering also that the value of the investment corresponded to R$ 160,000.00 (one hundred and sixty thousand reais). From the socio-environmental point of view, the initiative is seen as a major advance, since the campus stands out among other campi when investing on this important renewable energy project.